Features of communicative in Arabic grammar - Al-maqabelah, Sefaa Ali (Arab Journal for Sciences and Research Publishing, 2020)
This research links between Arabic grammar and communicative linguistics, then it deals with models of Arabic grammar to show the features of communication in its modern concept with (Roman Jacobson), and the extent of its influence on grammatical thinking among Arabs, so the research shows the impact of the elements of communication (sender, receiver, linguistic message, and reference And Sunnah (code and coding) in producing grammatical and grammatical rulings at one time, and in substituting verbal linguistic performances - through coding, coding, and reference represented in context - at other times, the research highlights the importance of each component of communication in building speech in the Arabic grammar, The effect of that The element in the grammatical opinions that they relied upon when retiring the language, and if they did not present it in independent or ad hoc studies at that time, the research discussed models of grammatical evidence, according to the descriptive analytical method, to arrive at several results centered on the presence of the elements of communication as mentioned by (Jackson) clearly in Arabic grammar, where the importance of the speaker and the addressee is evident in building the linguistic message that the Arabic grammar scholars made their interest lie, and they made full use of communicative elements for their construction, and these elements were represented by them in four pillars (the message, the speaker, the addressee, and context of the case).